2015
DOI: 10.1590/1982-0224-20140146
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal biomarkers responses of Astyanax jacuhiensis (Cope, 1894)(Characiformes: Characidae) from the middle rio Uruguai, Brazil

Abstract: Due to intense agricultural activity in the rio Uruguai (South Brazil), there is the potential for aquatic contamination by agrochemicals. In this region, there are many reservoirs to meet the water demand for rice fields, forming lentic environments. In line with this information, the aim of this study was to show a comparative analysis of some biomarkers, such as lipid peroxidation (TBARS), gluthatione S-transferase (GST), non-protein thiols (NPSH), amino acids (AA) and piscine micronucleus tests (MNE) in As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 49 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In the China, Tan et al (2020) reported the occurrence of atrazine (4.1 μg L −1 ) in surface water, exceeding 2 times the limit allowed by the Ministry of Health (2007). In Brazil, in aquatic ecosystems, have been detected atrazine concentrations (2.7, 2.89, 4.1, 4.92 and 9.33 μg L −1 ) until 4.66 times higher than the permitted by Brazilian legislation for freshwater, as well as levels that exceed the value stipulated by United State and China (Armas et al 2007;Della-Flora et al 2019;Loro et al 2015;Moreira et al 2012). This is worrying, since the results obtained in the present study indicate that the concentration of 2 μg L −1 caused Although atrazine has been detected in low concentrations in surface waters in several countries, it must be monitored in environmental studies, since it has also been detected with values above what is allowed (Table 3), because your presence in aquatic environments can affect the ecosystem, causing an imbalance in the environment (Albuquerque et al 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the China, Tan et al (2020) reported the occurrence of atrazine (4.1 μg L −1 ) in surface water, exceeding 2 times the limit allowed by the Ministry of Health (2007). In Brazil, in aquatic ecosystems, have been detected atrazine concentrations (2.7, 2.89, 4.1, 4.92 and 9.33 μg L −1 ) until 4.66 times higher than the permitted by Brazilian legislation for freshwater, as well as levels that exceed the value stipulated by United State and China (Armas et al 2007;Della-Flora et al 2019;Loro et al 2015;Moreira et al 2012). This is worrying, since the results obtained in the present study indicate that the concentration of 2 μg L −1 caused Although atrazine has been detected in low concentrations in surface waters in several countries, it must be monitored in environmental studies, since it has also been detected with values above what is allowed (Table 3), because your presence in aquatic environments can affect the ecosystem, causing an imbalance in the environment (Albuquerque et al 2020).…”
Section: Discussionmentioning
confidence: 96%
“…However, this herbicide still is widely used in other countries, an example Brazil, where the National Environmental Council (CONAMA, Resolution 357/2005, updated and modified by Resolution 430/2011) establishes that the maximum concentration of atrazine for freshwater (surface waters intended for human consumption and the protection of aquatic life) must be 2 μg L −1 . Despite this established value, concentrations higher than the recommended have been found in aquatic environments (Armas et al 2007;Della-Flora et al 2019;Loro et al 2015;Moreira et al 2012).…”
Section: Introductionmentioning
confidence: 98%